Obstetric risk in pregnancy interacts with hair cortisone levels to reduce gestational length - Musana, Joseph; Cohen, Craig R.; Kuppermann, Miriam; Gerona, Roy; Wanyoro, Anthony; Aguilar, David; Santos, Nicole; Temmerman, Marleen; Weiss, Sandra J. (Frontiers in Global Women's Health, 2022)
Background Maternal psychological stress has been linked to preterm birth. However, the differential contribution of psychological stress versus stress hormones is not clear. Studies focus primarily on perceived stress and cortisol, with few assessing its inter-convertible hormone cortisone. Furthermore, little is known about the potential moderating roles of obstetric risk and fetal sex in the relationship between maternal stress and gestational length. This gap in knowledge is particularly evident for rural women who typically experience chronic multiple stressors during pregnancy. We explored the relationship of hormonal and psychological stress to gestational length and the effects of obstetric risks and fetal sex on this relationship among Kenyan pregnant women. Methods The sample included 130 women recruited between 22 to 28 weeks gestation. They completed a clinical and sociodemographic questionnaire together with the Perceived Stress Scale and provided a hair sample for cortisol and cortisone assay. Women underwent an ultrasound to assess weeks of gestation. At delivery, their pregnancy-related health problems were identified using information extracted from medical records to compile each woman's number of pregnancy risks on the Obstetric Medical Risk Index (OMRI). Results Perceived stress and hair cortisol were not significant predictors of gestational length. However, a greater number of obstetric risks on the OMRI was associated with shorter gestational length. This effect was further explained by the interaction between obstetric risk and hair cortisone (B = 0.709, p = 0.02). Hair cortisone levels of mothers who had a shorter gestation were significantly higher in mothers with 2 or more risks on the OMRI but not among mothers with only one or no risks (t = 2.39, p = 0.02). Fetal sex had no relationship to gestational length and also had no moderating effect on the relationship between any stress-related metric and gestational length. Conclusion Cortisone levels may increase in anticipation of shorter gestation as a compensatory response to increased obstetric risk. Elevated cortisone may be a more sensitive marker of risk for early delivery than cortisol or psychological stress, with salience for both the male and female fetus.